Mahogany and Kadam planting farmers in South Kalimantan: the link between Silvicultural activity and stand quality - Kallio, M.H.; Krisnawati, H.; Rohadi, D.; Kanninen, M. (2011)
This paper examines the relationship between farmers’ socio-economic characteristics, silvicultural activity and the quality of their mahogany and kadam plantation stands in two independent case study villages in South Kalimantan Province, Indonesia. Data on farmers’ socio-economic characteristics and silvicultural practices were collected and analysed by village using descriptive statistics, Mann–Whitney tests and Spearman correlations. Mahogany planters with larger areas planted carried out more silvicultural practices. Kadam planters who had joined the farmer’s group earliest, had favourable or highly favourable attitudes towards tree planting, and whose households included more members gaining income were more active in silvicultural management. Approximately half of the studied mahogany and kadam plantations were of high quality. Most of the farmers conducted the recommended silvicultural practices, but just conducting them did not of itself cause the variation in the quality of stands. Pruning timing and recovery time after pruning, however, had an effect on the volume of potentially merchantable wood on medium quality mahogany sites. Further research is required on timing, frequency and methods used for the silviculture in order to improve the quality of stands. The policy implications drawn from this research include that farmers need to be provided with: (a) incentives to plant species with identified markets with reasonable price; (b) motivated extension officers; (c) improved access to production inputs; and (d) structures and mechanisms to assist them to organize and to develop activities, such as joint marketing.